A theoretical model for the rotational stiffness of storage rack beam-to-upright connections. (June 2017) - Zhao, Xianzhong; Dai, Liusi; Wang, Tuo; Sivakumaran, Ken Siva; Chen, Yiyi
Abstract: Experiments are generally used to investigate connection behaviour of steel storage racks, but the procedures are expensive and time-consuming. Various connections with complicated geometrical details necessitate simple and reliable design methods. This paper presents a mechanical model based on the component method to predict the initial rotational stiffness of beam-to-upright connections in cold-formed steel storage racks. In the model, five basic deformable components contributing to the initial rotational stiffness of beam-to-upright connections, are involved, i.e. tab in bending, upright wall in bearing, and upright wall in bending, beam-end-connector in bending and shear, upright web in shear. The mechanical model is validated against experiments, and the results show that the initial rotational stiffness values obtained from the mechanical model have a satisfactory agreement with the experimental results. Finally, based on the proposed mechanical model, main components influencing the initial rotational stiffness of connections are analysed in this paper. Highlights: A mechanical model is proposed to predict the rotational stiffness of beam-to-upright connections in steel storage racks. Five basic deformable components contributing to the initial rotational stiffness of the connections are identified. Detailed methods to evaluate the stiffness of equivalent springs representing five basic components are provided. The influences of different components on the initial rotational stiffness of the connections are investigated.